Human-Computer Interaction - INTERACT 2009 12th IFIP TC 13 International Conference, Uppsala, Sweden, August 24-28, 2009, Proceedigns Part I - Gross, Tom; Gulliksen, Jan; Kotzé, Paula; Oestreicher, Lars; Palanque, Philippe; Prates, Raquel Oliveira; Winckler, Marco (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2009)
The two volume set LNCS 5726 and LNCS 5727 constitutes the refereed proceedings of the 12th IFIP TC13 International Conference on Human-Computer Interaction, INTERACT 2009, held in Uppsala, Sweden, in August 2009. The 183 revised papers presented together with 7 interactive poster papers, 16 workshops, 11 tutorials, 2 special interest group papers, 6 demonstrations, 3 panels and 12 doctoral consortium papers were carefully reviewed and selected from 723 submissions. The 99 papers included in the first volume are organized in topical sections on accessibility; affectice HCI and emotion; child computer interfaces; ethics and privacy; evaluation; games, fun and aesthetic design; HCI and Web applications; human cognition and mental load; human error and safety; human-work interaction design; interaction with small and large displays; international and cultural aspects of HCI; mobile computing; and model-based design of interactive systems.